Corporate governance principles and their influence on sustainability reporting in Indonesian public companies: The moderating role of associations and regulators - Amin, Aminul; Wiyarni, Wiyarni; Kadarusman, Kadarusman (Edelweiss Applied Science and Technology, 2025)
This study examines the influence of corporate governance principles on the Sustainability Reporting Disclosure Index (SRDI), incorporating the moderating roles of regulators and industry associations. Using a quantitative panel data approach from Indonesian publicly listed companies between 2022 and 2024, the study evaluates ten governance principles: transparency, accountability, fairness, responsibility, independence, shareholder empowerment, legal compliance, openness, integrity, and sustainability. The results reveal that transparency, accountability, integrity, and legal compliance are the most influential factors in enhancing SRDI quality. Regulatory oversight by Indonesia’s Financial Services Authority (OJK) plays a more dominant moderating role than industry associations, demonstrating that institutional pressures significantly shape credible sustainability reporting practices. Theoretically, this study contributes to the advancement of stakeholder theory and institutional theory by developing the “Triple-Interaction Governance–Institutional–Disclosure” model, which captures the simultaneous interplay between governance mechanisms, institutional forces, and sustainability reporting quality. Practically, the findings underscore that collaboration among firms, regulators, and industry associations is essential to strengthen transparency, accountability, and sustainability legitimacy in emerging markets such as Indonesia.